Plastome phylogeny and early diversification of Brassicaceae - Guo, Xinyi; Koch, Marcus (BMC genomics, 2017)
The family Brassicaceae encompasses diverse species, many of which have high scientific and economic importance. Early diversifications and phylogenetic relationships between major lineages or clades remain unclear. Here we re-investigate Brassicaceae phylogeny with complete plastomes from 51 species representing all four lineages or 5 of 6 major clades (A, B, C, E and F) as identified in earlier studies.